Victimization as transformative experience: A phenomenological perspective - Pemberton, Antony (Theoretical criminology, 2025)
Dominant approaches to victimization define it in terms of (psychological) suffering and norm transgression. A critical approach endorses more-inclusive examinations of harm and turns to victims to hear and learn from their experiences. In this article, we illustrate how a phenomenological approach contributes to this endeavour and can illuminate often neglected aspects of victimization. We engage in a close reading of Susan Brison's Aftermath and other autobiographical works of severe victimization, integrating key phenomenological understandings of being and death by Martin Heidegger and Emmanuel Levinas in our analysis. We consider the implications of understanding victimization as an experience of a collapse of a meaningful world through the other's exploitation of victims’ existence.